Peran International Civil Aviation Organization (ICAO) Dalam Penanganan Kasus-Kasus Penembakan Pesawat Sipil Di Wilayah Berkonflik - Simamora, Rumla Yanti; Lestari, Maria Maya (PATTIMURA Legal Journal, 2024)
Introduction: The International Civil Aviation Organization (ICAO) acts as an organization that notifies civilian aircraft that will pass in conflict areas and also cooperates with other countries in increasing ICAO supervision so that similar cases do not occur. Purposes of the Research: To know the role of ICAO (International Civil Aviation Organization) in handling international aviation safety supervision and cases of shooting down civil aircraft in conflict areas. Methods of the Research: This type of research can be classified as a normative research type, this research uses research methods on the principles of international law. This research is a descriptive analysis, namely describing and analyzing the problems that have been put forward to describe an overview of the International Civil Aviation Organization in handling cases of shooting down civil aircraft in conflict areas related to international air law. Results of the Research: International civil aviation, especially when crossing conflict zones while the Civil Aviation Convention (known as the Chicago Convention) establishes a framework for civil aviation investigations, does not provide an appropriate legal and institutional framework for accountability, ICAO's role as a specialized agency of the United Nations which is required from time to time to refrain from violations. International political parameters in its diplomatic efforts